Americium preferred: lanmodulin, a natural lanthanide-binding protein favors an actinide over lanthanides. Issue 47 (29th November 2021) - Singer, Helena; Drobot, Björn; Zeymer, Cathleen; Steudtner, Robin; Daumann, Lena J.
Abstract : In need of environmentally friendly methods for the separation and recycling of lanthanides and actinides, the binding of the protein lanmodulin to lanthanides and actinides was studied using time resolved laser induced fluorescence spectroscopy. Abstract : The separation and recycling of lanthanides is an active area of research with a growing demand that calls for more environmentally friendly lanthanide sources. Likewise, the efficient and industrial separation of lanthanides from the minor actinides (Np, Am–Fm) is one of the key questions for closing the nuclear fuel cycle; reducing costs and increasing safety. With the advent of the field of lanthanide-dependent bacterial metabolism, bio-inspired applications are in reach. Here, we utilize the natural lanthanide chelator lanmodulin and the luminescent probes Eu 3+ and Cm 3+ to investigate the inter-metal competition behavior of all lanthanides (except Pm) and the major actinide plutonium as well as three minor actinides neptunium, americium and curium to lanmodulin. Using time-resolved laser-induced fluorescence spectroscopy we show that lanmodulin has the highest relative binding affinity to Nd 3+ and Eu 3+ among the lanthanide series. When equimolar mixtures of Cm 3+ and Am 3+ are added to lanmodulin, lanmodulin preferentially binds to Am 3+ over Cm 3+ whilst Nd 3+ and Cm 3+ bind with similar relative affinity. The results presented show that a natural lanthanide-binding protein can bind a major and various minor actinides with high relative affinity, paving the way to bio-inspired separation applications. In addition, an easy and versatile method was developed, using the fluorescence properties of only two elements, Eu and Cm, for inter-metal competition studies regarding lanthanides and selected actinides and their binding to biological molecules.